Problems of Islamic Education in The Era of Industrial Revolution 4.0 - Raodatul Jannah (Syntax Corporation Indonesia, 2022)
The existence of Islamic education in Indonesia has been around for a long time since the 13th century AD, but various problems have always accompanied Islamic education from the colonial colonial era, the Old Order, the New Order, Reformation, to the Industrial Revolution Era 4.0. especially in the midst of this era of industrialization, forcing all elements within the State and society based on digitalization and manufacturing. This is very much different from the paradigm of Islamic education which focuses on guiding humans so that they become Islamic-spiritual human beings who must be oriented towards technology and manufacturing. There are a number of problems that are still the